Pengaruh Influencer Review dan Bandwagon Effect terhadap Minat Beli Produk Pashmina Tencel pada Platform Tiktok - Aura Alfnavisa Az-Zahra; Sugeng Purwanto (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2026)
The rise of digital marketing has transformed consumer consumption patterns, where purchasing decisions are no longer solely based on price and product quality, but are also influenced by review content and the growing presence of paid buzzers that can shape consumer perceptions and purchase intentions. This study aims to examine the influence of influencer reviews and the bandwagon effect on the purchase intention of pashmina tencel products on TikTok. This research adopts a quantitative approach using a survey method, with data collected through online questionnaires distributed to 110 respondents selected using purposive sampling. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The findings indicate that influencer reviews have a positive and significant contribution to consumer purchase intention. Similarly, the bandwagon effect also demonstrates a positive and significant influence on purchase intention. The credibility of influencers plays a crucial role in building trust and shaping positive consumer attitudes, while the bandwagon effect reflects social influence that encourages consumers to follow popular trends, which in turn enhances their intention to purchase.